PENINGKATAN PENGETAHUAN PETANI MELALUI INOVASI TEKNOLOGI PEMANFAATAN VEGETASI SEKUNDER SEBAGAI BAHAN PUPUK ORGANIK UNTUK MENINGKATKAN KESUBURAN TANAH PADA LAHAN JAGUNG DI DESA WARAMBE KECAMATAN PARIGI KABUPATEN MUNA - Mila Rahni, Nini; Kadek Sutariati, Gusti Ayu; Wijayanto, Teguh; Zulfikar, Zulfikar; Hariaty Hasan, Rachmi (....-...., 2023)
The Internal Partnership Program (PKMI) for faculty service is conducted in Warambe Village, Parigi District, Muna Regency, Southeast Sulawesi, with the target audience being the Labotoro Farmers Group. The issues encountered by the farmers' group include poor soil fertility, specifically low-quality land, and a lack of knowledge regarding the production of organic fertilizers based on secondary vegetation. Additionally, there is a significant amount of agricultural waste and secondary vegetation available, but they have not been maximally utilized as raw materials for enhancing soil fertility and as a nutrient source for corn plants due to a lack of knowledge in this area. The proposed solution and targets are to provide technical guidance and demonstrate the production of organic fertilizers for soil fertility enhancement, as well as to transfer this technological innovation to the farmers. The dissemination and adoption process of this technology is expected to increase farmers' income through increased production of yellow corn crops. The results obtained from the provided solution include an 85% increase in the understanding and knowledge of the members of the farmers' group regarding the utilization of secondary vegetation for organic fertilizer and soil fertility enhancement in their corn fields. The technology of utilizing secondary vegetation has not been previously implemented by the partner group, so this activity has contributed to the farmers' knowledge and skills in improving land productivity, especially within the Labotoro Farmers Group